Implementation of the National Flight Security Program in UPBU Djaluddin Gorontalo - Arifin Tahir; M Jamal Nganro; DODIKISWANTO J. MANO (Governance: Jurnal Ilmu Administrasi Publik, 2023)
The purpose of this study was to analyze the factors that determine the Implementation of the National Aviation Security Program at the Djalaluddin Gorontalo Airport Operator Unit (UPBU). This research uses qualitative research methods, the type of research is descriptive research. Data was collected by means of observation, interviews and documentation. The results of this study indicate that the factors that support the implementation of the national aviation security program at the Djalaluddin Gorontalo Airport Operator Unit (UPBU) are communication in the form of optimal socialization using various media including social media, disposition or attitude of implementers who have high commitment and bureaucratic structure in the form of good delegation of authority. The inhibiting factors in the implementation of the national aviation security program at the Djalaluddin Gorontalo Airport Operator Unit (UPBU) are communication with relevant agencies that have not been optimal, resources that have not met expectations in the form of lack of personnel, procedures that are still considered troublesome for passengers because there are two Security Check Point (SCP) and inadequate facilities and bureaucratic structure in the form of protocol activities that are entrenched in Gorontalo.